Association of Added Sugars Intake with Micronutrient Adequacy in US Children and Adolescents: NHANES 2009–2014 - Fulgoni, Victor L (Curr Dev Nutr, 2019)
BACKGROUND: A concern about the excessive consumption of added sugars is the potential for micronutrient dilution, particularly in children and adolescents; however, the evidence is inconsistent. OBJECTIVE: We examined the associations between added sugars intake and micronutrient adequacy in US children and adolescents using data from NHANES 2009–2014. METHODS: Children and adolescents aged 2–18 (n = 7754), 2–8 (n = 3423), and 9–18 y (n = 4331) were assigned to deciles of added sugars intake based on the average of 2 d of dietary recall. Usual intake of micronutrients was determined using 2 dietary recalls and the National Cancer Institute method. Within each age group, regression analyses were used to assess the relationship between added sugars intake decile and percentage of the population below the estimated average requirements (EARs) for 17 micronutrients. RESULTS: Deciles of added sugars intake (percentage of calories) ranged from <6.4 to >22.8 among children and adolescents aged 2–18 y, with a median intake of 13.3% of calories. Significant positive associations (P < 0.01) between added sugars intake and percentage of the population (aged 2–18 y) below the EAR were found only for calcium, magnesium, and vitamin D. These associations virtually disappeared after dropping the 2 highest and lowest deciles of intake, suggesting a threshold effect; intakes below approximately 19% of calories from added sugars were generally not associated with micronutrient inadequacy. CONCLUSIONS: As added sugars intake increased, there was a threshold above which an increase in the prevalence of inadequate intakes for calcium, magnesium, and vitamin D among US children and adolescents was observed. However, even at the lower deciles of added sugars, large percentages of the population were below the EAR for these nutrients, suggesting that adequate intakes of these nutrients are difficult to achieve independent of added sugars intake.